1996
DOI: 10.1007/bf02247337
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the biphasic locomotor response to ethanol in high and low responders to novelty: a study in nijmegen wistar rats

Abstract: The aim of the study was to investigate the biphasic locom otor response to ethanol in rats. Based on the recent finding that high responders to novelty (HR) and low responders to novelty (LR), selected from an outbred Nijmegen W istar rat population, show differences in ethanol intake and preference, it was ini tially investigated to what extent H R and L R differ in their locom otor response to ethanol, A dose-response curve (0.2-2.0 g/kg, IP) was established using stan dardized activity boxes. H R showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…Previous research has found that novelty-induced activity can serve as a predictive variable for a rat's sensitivity to the behavioral effects of abused drugs. This list of behaviors includes self-administration [14,15,29], drug discrimination [13], context conditioning [17], bar-press suppression [6], and locomotor activity [16,29]. Much of the research just cited reports a positive relation between reactivity to novelty and the subsequent behavioral effect of interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has found that novelty-induced activity can serve as a predictive variable for a rat's sensitivity to the behavioral effects of abused drugs. This list of behaviors includes self-administration [14,15,29], drug discrimination [13], context conditioning [17], bar-press suppression [6], and locomotor activity [16,29]. Much of the research just cited reports a positive relation between reactivity to novelty and the subsequent behavioral effect of interest.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, rats that are more activated by exposure to a novel environment (HR) more readily self-administer amphetamine and are more sensitive to the locomotor-stimulant effects of amphetamine [29]. Novelty-induced activity has been found to also predict such behavioral effects as activity induced by cocaine and caffeine [16], ethanol-induced activity and ethanol self-administration [14,15], amphetamine-conditioned hyperactivity to contextual stimuli [17], cueing effects of amphetamine [13] and amphetamine barpress suppressant effects [6].Another factor contributing to the interest in novelty-induced activity is the potential insight it may provide into the behavioral and neural substrates underlying individual differences in drug abuse vulnerability. This idea is based, in part, on the assumption that the predictive relation just described likely refl ects an overlap in the mechanism(s) responsible Published in Physiology & Behavior 72 (2001) Abstract: An increasing body of research has focused on isolating factors that predict or alter individual differences in the behavioral and neural processes mediating the effects of abused drugs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The activating effects of systemic administration of ethanol have typically been shown in mice (Read et al, 1960;Frye and Breese, 1981;Crabbe et al, 1982;Masur et al, 1986;Aragon et al, 1992a;Phillips and Shen, 1996;Correa et al, 1999aCorrea et al, , 2000Correa et al, , 2001Correa et al, , 2004b. Although some studies have shown that selectively bred alcohol-preferring rats can show ethanol-induced increases in locomotion (Paivarinta and Korpi, 1993;Colombo et al, 1998;Rodd et al, 2004), in most previous studies, peripheral administration of ethanol to other strains of rats failed to stimulate locomotor activity, and generally has resulted in a suppression of motor activity (Frye and Breese, 1981;Masur et al, 1986;Waller et al, 1986;Spivak et al, 1987;Aragon et al, 1989;Gingras and Cools, 1996;Correa et al, 2003a). More recently, through the use of intraventricular administration of ethanol directly into the brain, it has been demonstrated that central administration of ethanol in rats can induce locomotor activation (Correa et al, 2003a, b) and also increased operant responding on a DRL30 schedule, which is a sign of behavioral stimulant effects (Arizzi et al, 2003).…”
Section: Effects Of Snr Infusions Of Ethanolmentioning
confidence: 99%
“…The excitatory effects of ethanol have been phenotypically characterized in several different species, yet the molecular mechanism by which ethanol acts as an excitatory drug remains uncharacterized (Gingras and Cools 1996;Addicott et al 2007;Arias et al 2009;Beckstead and Phillips 2009;Kong et al 2010;Rose et al 2013). Using the model organism C. elegans, we developed a hypercontraction assay to study both the excitatory effects of ethanol and the tolerance that develops to these effects.…”
Section: Discussionmentioning
confidence: 99%